Students' mental health status during COVID-19 outbreak - Azizah Alqahtani; Monira Almegren (Taez University, 2024)
Objectives: This study aimed to survey the mental health of female students at Princess Nourah bint Abdulrahman University during the COVID-19 outbreak and explore the relationship between anxiety, depression, and OCD among them. Methods: During the COVID-19 pandemic, an online survey was distributed to students at Princess Nourah University, a women's university in Saudi Arabia, via email A total of 4151 students completed the survey. The survey included a series of questionnaires including The Yale-Brown Obsessive-Compulsive Scale (Y-BOCS), the Patient Health Questionnaire depression scale, and the GAD-7 anxiety scale. Results: Students tended to show high levels of depression, anxiety, and OCD during the COVID-19 pandemic. Anxiety, depression, and OCD were positively related. Furthermore, scores on the obsessive-compulsive disorder (OCD) scale moderated the relationship between scores on the anxiety and depression scales. Conclusion: This study revealed a significantly high prevalence of depression, anxiety, and OCD among students during the COVID-19 outbreak. Scores on the three scales are related positively and OCD moderated the relationship between anxiety and Depression.